2023
DOI: 10.1088/1748-9326/acbb1b
|View full text |Cite
|
Sign up to set email alerts
|

Review of black carbon emission factors from different anthropogenic sources

Abstract: Particulate black carbon (BC) affects global warming by absorbing the solar radiation, by affecting cloud formation, and by decreasing ground albedo when deposited to snow or ice. BC has also a wide variety of adverse effects on human population health. In this article we reviewed the BC emission factors (EF) of major anthropogenic sources, i.e., traffic (incl. marine and aviation), residential combustion, and energy production. We included BC EFs measured directly from individual sources and EFs derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 177 publications
0
7
0
Order By: Relevance
“…Population size: With the comprehensive lifting of the "three-child" policy in China in 2021, the Yellow River Basin may experience a short-term surge in its population, with a declining trend before and after the population peak (Rönkkö et al 2023). Based on the population growth rate of China (Yue et al 2021) and the actual economic and social development of the Yellow River Basin, the parameters for the low and high rates in the forecasting interval from 2020 to 2025 were set to 0.4% and 0.5%, respectively, with those from 2026 to 2030 set to 0.2% and 0.25%, and those from 2031 to 2035 set to -0.1% and 0%.…”
Section: Scenario Settingmentioning
confidence: 99%
“…Population size: With the comprehensive lifting of the "three-child" policy in China in 2021, the Yellow River Basin may experience a short-term surge in its population, with a declining trend before and after the population peak (Rönkkö et al 2023). Based on the population growth rate of China (Yue et al 2021) and the actual economic and social development of the Yellow River Basin, the parameters for the low and high rates in the forecasting interval from 2020 to 2025 were set to 0.4% and 0.5%, respectively, with those from 2026 to 2030 set to 0.2% and 0.25%, and those from 2031 to 2035 set to -0.1% and 0%.…”
Section: Scenario Settingmentioning
confidence: 99%
“…Combining the relevant literature, this study selects seven factors -digital economy, technological innovation, industrial structure adjustment, economic development, population, foreign investment, and urbanization -to study their impact on carbon emissions (Liu et al, 2023;Rönkkö et al, 2023;Sun and Wu, 2023). The panel data of 57 prefecture-level cities in the Yellow River Basin from 2012 to 2021 are statistically analyzed, and the entropy method is used to process the influencing factors (see quantile regression with fixed effects, and the specific expression is as follows:…”
Section: Panel Quantile Regressionmentioning
confidence: 99%
“…In particular, for the period 2017-2021, we considered atmospheric observations of equivalent black carbon (eBC), CO and CO 2 , in correlation with the direction and speed of the local wind fields. eBC is a component of incomplete combustion by products commonly referred to as soot and causes major environmental issues [24][25][26]. Recently, model results and field measurements have shown that aerosols may have important climatic impacts [13].…”
Section: Introductionmentioning
confidence: 99%